Silver diamine fluoride in paediatric dentistry practice: Silver diamine fluoride dalam praktik kedokteran gigi anak - Fajriani; Marhamah; Sherly Horax; Hafsah Katu; Siti Rachmatiara Dwi Destiarini (Makassar Dental Journal PDGI Makassar, 2023)
Dental caries is one of the most common diseases in children worldwide. In the age range of 3-6 years, nine out of ten children in Indonesia experience dental caries. Silver diamine fluoride (SDF) is an option of caries management to inhibit caries activity in primary teeth. The SDF has received a lot of attention recently due to its ease of application, effectiveness, affordability, and short uptime. This article aims to review the treatment of silver diamine fluoride in pediatric dentistry.